(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the characteristics of endoscopic ultrasound in chronic pancreatitis at the Gastroenterology and Hepatology Center, Bach Mai Hospital, from 2024-2025. Subjects and methods: A cross-sectional descriptive study was conducted on 40 patients with chronic pancreatitis diagnosed and treated at the Gastroenterology and Hepatology Center, Bach Mai Hospital, from October 2024 to June 2025. Endoscopic ultrasound images were described according to the ECP-2019 modified 2023 criteria. Results: Regarding patient characteristics, the majority of patients were in the 40-60 age group (60%), with the youngest being 31 and the oldest 97; only two patients were female. The most common symptom was abdominal pain (95%). On endoscopic ultrasound, 100% of patients had pancreatic parenchymal lesions and hyperechoic strands, primarily hyperechoic foci and parenchymal calcifications, with rates of 95% and 77.5% respectively. Pancreatic cysts were the least common at 55%. The majority of patients had main pancreatic duct lesions (70%), with 100% of these cases showing main pancreatic duct dilation. The ECP-2019 modified 2023 criteria helped diagnose chronic pancreatitis in 16/20 cases (80%) suspected according to Rosemont (2007) (corresponding to early-stage chronic pancreatitis). Conclusion: The revised ECP-2019 criteria (2023 update) are effective in detecting and stratifying early stages of chronic pancreatitis.